Investigation on Wintry Thermal Comfort in Traditional Houses of Nepalese Three Climatic Regions - Gautam, Basudev; Rijal, Hom Bahadur; Shukuya, Masanori (Journal of the Institute of Engineering, 2020)
The traditional houses are well adapted to the climate and socio-culture using local building materials and techniques. However, traditional practices are being replaced by the artificial materials, modern design and new technology. It requires strong policies to sustain the traditional architecture. The objectives of this study are to evaluate the thermal condition of traditional houses and to estimate the comfort temperature of residents. The thermal comfort survey was conducted during winter in the traditional houses. The thermal sensation votes were collected from 275 people in cold, temperate and sub-tropical climatic regions. This study was revealed that the mean indoor air temperature in cold climatic region is 12.3°C, which was 9.5K and 4.4K lower than sub-tropical and temperate climates. The comfort temperature of the residents in the cold climate was 13.9°C, which was 8.8K and 3.8K lower than sub-tropical and temperate climates. The mean clothing insulation in cold climate was 1.63 clo which was 0.48 clo and 0.31 clo higher than sub-tropical and temperate climates. It concludes that the people were well adapted to each climate with clothing adjustments and made themselves satisfied with the thermal condition of their houses.